Manajemen Pendidikan Islam dan Problematikanya - Majdudin Nurul Huda (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
The article discusses the challenges and solutions in managing an Islamic junior high school (MTsN) in Piyungan, Bantul, Yogyakarta. It emphasizes the role of school leaders in developing human resources and addressing internal and external issues. The frequent change of school principals within a short period has impacted the school's development. The research employs qualitative descriptive methodology, highlighting the significance of conflict management, educational management, and human resource management. Common problems include accreditation preparation, building development, principal rotation, and teaching management. Solutions proposed include team collaboration, transparent fund management, and enhancing students' life skills through improved facilities. The study concludes that effective leadership and coordinated efforts are vital to addressing these challenges and achieving the school's objectives.